A New Solution of Intermediate Cosmological Inflation with the Effect of Scalar Field (The Chittagong University Journal of Science, 2021)
According to the inflationary model, the universe had a brief period of extraordinarily rapid expansion or inflation during which its diameter increased by a factor at least 1025 times larger than previously thought. In this work an analysis is given on inflationary universe, which expands at a rate intermediate between that of power-law and exponential inflation. We have examined the model of Barrow which is solved exactly and leaded to power law inflation. We have tested a new potential by applying the scalar field using the equation of motion and found some new interior solutions.The Chittagong Univ. J. Sci. 40(1) : 112-121, 2019